The Fiftieth Year of Independent Kenya: Elections, Righteousness and Churches. (January 2016) - Knighton, Ben
The year 2013 has proved to have been a turning-point for the nation of Kenya in a number of ways. It was a year when Kenya chose peace rather than democracy, but insecurity rather than accountability, cooperation with East rather than West, and nationalism above free speech. The article focusses on two moments framed by the elections: the armed attack on the Westgate shopping mall, and the funeral of the previous Archbishop. The newly elected government utilized these events to frustrate the International Criminal Court. It draws from eye-witness presence in addition to an analysis of print and other media, and it finds that peace and nation-building were bought at the price of insecurity and the aspirations that eventually inaugurated a new constitution. The churches were this time minor players, and with the death of David Gitari were shown almost bereft of the courageous spirit that had been the voice of disempowered Kenyans.